Faktor-faktor yang mempengaruhi pendapatan pekerja wanita sebagai Ibu rumah tangga - Rio Christoper; Rosmiyati Chodijah; Yunisvita Yunisvita (Department of Development Economics, Universitas Sriwijaya, 2017)
The purpose of this research is to analyze the factors affecting female workers as housewives in Palembang. The independent variables in this research are the level of education, work hours, marriage status, work experience, financial dependency and age. This research was conducted in Palembang, South Sumatra Province. This research used primary data with samples of 97 respondents. The method used in this analysis was the Ordinary Least Squared (OLS) by using E-views 9.0. The result showed that the level of education and work hours had significant and positive effect on the income of female workers from poor households. For the age variable had significant and negative effect on the income of female workers from poor households. Meanwhile, the marriage status variables had no difference income between married and single female workers. For work experience had no significant and negative effect on the income of female workers from poor households, and for financial dependency had positive effect but no significant on the income of female workers from the poor households in Palembang.